Students’ Digital Technology Access and Utilization for Learning Listening Skills - Tesfaye W, Betelhem; Banteyerga A, Hailom (Universitas Pendidikan Mandalika, 2025)
This study examined the access and use of digital technology and the approach preference and experience in learning listening skills among undergraduate students at Addis Ababa Science and Technology University (AASTU). The researchers conducted a case study with a randomized sample of students. They collected data through a questionnaire (292 students) and focus group discussions. The data was analyzed using descriptive statistics and thematic analysis. Though students possessed smartphones, computers, and internet access, inconsistent Wi-Fi coverage presented challenges. A mixed-methods approach revealed a preference for technology-enhanced learning, with students appreciating its potential for authentic accents and fluency practice. However, traditional teacher-read approaches remained valuable for comprehension and familiarity. While comfortable with technology, students had not fully explored its potential for language learning. Limited listening practice and exposure to diverse accents were highlighted. Integrating diverse listening materials, technology-assisted practice, and differentiated instruction based on English language proficiency is recommended to create a more effective and engaging language learning environment that harnesses the power of technology without neglecting the comfort of familiar methods. The research urges teachers to leverage students' tech savvy and access to enhance listening instruction by intentionally embracing diverse digital tools and materials beyond classic classroom limitations.